P95 Oxygen delivery in an acute hospital setting. (16th November 2010) - Maycock, J; Ellis, K; Mullholland, P; Bate, L; Sadananda, V; Nazareth, D; Agarwal, S; Stockton, P
Abstract : Background: Oxygen is one of the most widely used drugs in secondary care. The National Patient Safety Agency (NPSA), UK issued guidance1 ensuring safer management of oxygen delivery. Many individuals do not see oxygen as a drug and hence prescribing oxygen within most Trusts has been poor. This study assesses Health Care Professionals (HCPs) knowledge of the basic principles of oxygen delivery in an acute medical setting, to ensure the safe use of oxygen and to inform a Trust Oxygen Steering Group in order to target educational sessions appropriately. Method: A questionnaire listing 10 common scenarios, based on the BTS guidelines2 was administered to a random selection of doctors and nurses (Abstract P95 Table 1 ). Responses were evaluated by a panel of Respiratory Physicians. For each scenario respondents indicated whether they would give oxygen, appropriate target saturations, delivery device to be used and the flow rate. Results: 139 HCPs completed the questionnaire (41% junior doctors, 59% nurses). The results are summarised below. Common mistakes included The use of non-rebreather mask instead of bag and mask in cardiac arrest situations Failing to identify the use of high flow oxygen in the conservative management of patients with a pneumothorax and Failing to recognize the use of Venturi masks in COPD patients. Conclusions: Most healthcare professionals understand the indication for the use of oxygen. However, knowledge of the appropriate use of delivery devices and target saturations was noted to be poor. Targeted educational sessions have been developed to address the above issues. We are currently in the process of trialling a new Kardex to ensure that all oxygen used on the ward within our Trust is prescribed. A Hospital Oxygen Steering Group is being set up with the function of overseeing the management and prescription of oxygen.